2015
DOI: 10.1371/journal.pone.0131254
|View full text |Cite
|
Sign up to set email alerts
|

CT Attenuation Features of Individual Calcified Coronary Plaque: Differences among Asymptomatic, Stable Angina Pectoris, and Acute Coronary Syndrome Groups

Abstract: BackgroundCoronary artery calcium (CAC) assessed by non-contrast cardiac CT has been shown to be an independent factor from the Framingham risk factors in predicting cardiovascular events. However, many patients with acute coronary syndrome (ACS) have low CAC score. A recent study that re-analyzed the previous CAC CT scan of MESA cohort showed that in subjects with global lower density, CAC was associated with higher risk of ACS. We aimed to further evaluate the characteristics of CAC attenuation features in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…A recent clinical CT study that examined the predictive value of both calcium density (standard CAC Agatston score) and plaque calcium density showed that although the CAC score was positively and independently associated with CV disease risk, at any level of CAC volume, CAC density was inversely and significantly associated with CV disease risk (12,33), as we found in our study. In addition, a recent study showed that a CAC score of zero at baseline in an asymptomatic population with no known CV disease was associated with low CAC progression over the 5year period.…”
Section: Calcification and Plaque Vulnerabilitysupporting
confidence: 83%
“…A recent clinical CT study that examined the predictive value of both calcium density (standard CAC Agatston score) and plaque calcium density showed that although the CAC score was positively and independently associated with CV disease risk, at any level of CAC volume, CAC density was inversely and significantly associated with CV disease risk (12,33), as we found in our study. In addition, a recent study showed that a CAC score of zero at baseline in an asymptomatic population with no known CV disease was associated with low CAC progression over the 5year period.…”
Section: Calcification and Plaque Vulnerabilitysupporting
confidence: 83%
“…Dense calcification is considered to contribute to worse cardiovascular prognosis in a different manner from spotty calcification, for example, by increasing vascular stiffness and reducing coronary flow reserve [ 29 ]. In fact, contrary to the findings of the non-CKD population [ 11 , 12 ], Bellasi et al have recently reported that the higher CAC density was associated with an increased risk of all-cause mortality in a cohort of 125 prevalent hemodialysis patients [ 30 ], suggesting that clinical relevance of CAC density in patients with kidney disease is different from those without kidney disease. Further follow-up studies are needed to elucidate the relationship between CAC density and cardiovascular prognosis in non-dialysis CKD patients.…”
Section: Discussionmentioning
confidence: 81%
“…In this context, the two previous studies of primarily the non-CKD population examined the CAC density [ 11 , 12 ]. These studies found that the risk of coronary artery disease increased as the CAC density decreased, suggesting that high-density calcified plaques may be protective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that density scores that can be retrospectively derived from the Agatston score and volume score are independently associated with increased coronary heart disease [22,23]. Our previous report also found that the CAC plaque in the ACS group had a lower and homogenous attenuation compared to subjects without symptoms or with chronic stable angina [24]. However, the impact of TRF and CAC burden among the three groups was not well eliminated.…”
Section: Discussionmentioning
confidence: 77%